2015 European Conference on Networks and Communications (EuCNC) 2015
DOI: 10.1109/eucnc.2015.7194124
|View full text |Cite
|
Sign up to set email alerts
|

Federated identity in real-life applications

Abstract: This paper describes scenarios and services based on Federated Identity technology. The authors emphasize the Single Sign On mechanism, in which a user's single authentication credential is used to log in once without being prompted to authenticate again to other systems. The overview of Federated Identity and a Federated Identity Management System is presented first. Next, federation approaches used in different fields of human activity are discussed. A few examples of such domains are presented: E-health, E-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…al verified solutions based on federated identity with circle of trust amongst IdPs. They concluded that federated identity provides for enhanced security with better service for users [5]. Gines Dolera Tormo et.…”
Section: Related Workmentioning
confidence: 99%
“…al verified solutions based on federated identity with circle of trust amongst IdPs. They concluded that federated identity provides for enhanced security with better service for users [5]. Gines Dolera Tormo et.…”
Section: Related Workmentioning
confidence: 99%